The Role of Lifestyle, Advertising, and Discount on Impulsive Buying (Survey of Tokopedia Application Users in Kuningan Regency) - Oktaviani, Winda; Ahman, Eeng; Komarudin, Munir Nur; Nasser (International Journal Administration, Business & Organization, 2024)
The intent of this study is to assess the impact of lifestyle, advertising, and discounts on impulsive purchases among Tokopedia application users in Kuningan Regency. The study methodology used in this research is descriptive and verification research methods with a data-driven survey approach. The demographic of the study composed of all people in Kuningan Regency who use the Tokopedia application. The sample size is 100 respondents, selected using purposive sampling techniques. The criteria for respondents include those who have used the Tokopedia application at least twice. The data used in obtained through surveys distributed to respondents who met the specified criteria. The results of the study show that lifestyle, advertising, and discounts have a positive and significant effect on impulsive buying. Advertising in particular, exerts a substantial positive and significant impact on impulsive buying.